Peran Bahasa Dalam Mempertahankan Kedekatan Dalam LDR: Strategi Komunikasi Dalam Mempertahankan Kedekatan Pada Hubungan (LDR) - Armeta Armeta; Daffa Nasywa Afriani; Indra Abdul Majid; Renitadewi Kusumah Wardani; Siti Hamidah (STIKes Ibnu Sina Ajibarang, 2024)
In the era of globalization that marks the existence of long-distance relationships (LDR), the role of language becomes an important focal point in understanding the dynamics of interaction between couples separated by geographical distance. This research uses Systematic Literature Review with Prism Method with the help of qualified google scholar. The results of the analysis are based on (23) twenty three relevant articles. Through the systematic literature review process within the span of last five years, highlighting the complexity of interpersonal communication in the context of LDR. This article discusses the extent of the role of language in LDR by using a sociolinguistic approach, emphasizing the importance of openness, honesty. and intensity of communication as the main factors in maintaining the relationship. Therefore, language is not only a means of communication, but also a foundation that builds and maintains emotional closeness between couples in LDR relationships, and provides insight into strategies that can be used to overcome problems that arise in these situations.